The influence peddlers - Kaddour, Hédi (Margellos world republic of letters book., 2017)
The eagerly awaited English translation of Kaddour's award-winning novel of clashing cultures during the French colonial years Gather together French colonialists, young nationalists eager for independence, and local Maghreb leaders in a small North African city of the 1920s. Bring a collection of brash American filmmakers and celebrities into the picture. Dangerous cultural collisions are the inevitable result in Hédi Kaddour's best-selling novel of French colonial rule and its persisting legacy of human chaos and cultural tragedy. In this commanding novel, the author plumbs the contradicti.